2017
DOI: 10.1007/s00384-017-2873-x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoradiotherapy changes the size criterion for predicting lateral lymph node metastasis in lower rectal cancer

Abstract: The cutoff size for determining lateral lymph node metastasis was smaller in the CRT group than in the non-CRT group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…While the role of nCRT for LPNM has become clearer in recent years, it is well recognized that nCRT cannot eliminate all malignant cells within LPNs. The results of this study suggest that LPNM is influenced by both post-nCRT size and the sensitivity of LPN classification [19,23,24]. Oh et al [19] reported that persistent LPNs ≥ 5 mm on post-nCRT MRI were more significantly associated with residual tumour metastasis than responsive LPNs after nCRT (61.1% vs 0%, P = 0.001), and multivariable analysis revealed post-nCRT LPN size to be a significant and independent risk factor for LPNM (OR = 2.390; 95% CI = 1.104-4.069, P = 0.001).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While the role of nCRT for LPNM has become clearer in recent years, it is well recognized that nCRT cannot eliminate all malignant cells within LPNs. The results of this study suggest that LPNM is influenced by both post-nCRT size and the sensitivity of LPN classification [19,23,24]. Oh et al [19] reported that persistent LPNs ≥ 5 mm on post-nCRT MRI were more significantly associated with residual tumour metastasis than responsive LPNs after nCRT (61.1% vs 0%, P = 0.001), and multivariable analysis revealed post-nCRT LPN size to be a significant and independent risk factor for LPNM (OR = 2.390; 95% CI = 1.104-4.069, P = 0.001).…”
Section: Discussionmentioning
confidence: 85%
“…Oh et al [19] reported that persistent LPNs ≥ 5 mm on post-nCRT MRI were more significantly associated with residual tumour metastasis than responsive LPNs after nCRT (61.1% vs 0%, P = 0.001), and multivariable analysis revealed post-nCRT LPN size to be a significant and independent risk factor for LPNM (OR = 2.390; 95% CI = 1.104-4.069, P = 0.001). Yamaoka et al [23] also found that in the nCRT group, the optimal cut-off value of post-nCRT LPN size was 5 mm, with a sensitivity of 71.4% and specificity of 85.3% for positive LPNM. Inoue et al [24], however, considered a 7 mm cut-off more appropriate.…”
Section: Discussionmentioning
confidence: 93%
“…There are some limitations to this study: it is a retrospective study based on a case series collected over 11 years; sample size is relatively small (104) even though comparable to various other publications5 21; a small number of events occurred during follow-up as expected in this setting. On the other hand, the fact that all samples are from a single centre with few dedicated surgeons, oncologists and subspecialised pathologists, thus minimising variability in treatment and histology protocols, should be considered as a strength.…”
Section: Discussionmentioning
confidence: 97%
“…Ishihara et al reported that the incidence of LLN metastasis was estimated to be 8.1% (18/222) even after preoperative CRT. Yamaoka et al also reported that LLN metastasis was detected in seven out of 19 patients who underwent preoperative CRT, suggesting preoperative CRT followed by ME alone is not sufficient, especially when LLN involvement is clinically suspicious . Ishihara's group carried out TME + LLND for patients with swollen LLN following preoperative CRT .…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Akiyoshi's group reported that the optimal cut‐off value before CRT was 8 mm . Yamaoka reported an optimal cut‐off value of 6.0 mm, with a sensitivity of 78.5% and a specificity of 82.9% . Before the start of preoperative treatment, accurate estimation of LLN size by MRI is useful.…”
Section: Surgical Treatmentmentioning
confidence: 99%